Needs Assessment of Public Special Education Schools in Cebu City, Philippines - Sayson, Yolanda C. (JPAIR Institutional Research, 2016)
Special Education (SpEd) teachers face difficulties in their roles of addressing issues in response to the demands of a rapidly changing society and profession. The study aimed to evaluate the programs and services of public special education schools in the Division of Cebu City, Philippines. The study employed a descriptive method using a modified researcher-made questionnaire. The study revealed that the six public special education schools were into special class programs or self-contained program. Almost all the public SpEd schools served mental deviates and children with sensory disabilities. On the other hand, one SpEd school accommodated students with emotional and behavioral problems, multiple disabilities and other health-related problems. On the number of students with disabilities and their educational levels, there is a total of 444 students in the six public Sped schools, 374 elementary level and 70 in high school. Two hundred ten of the students are mentally deviated (56.1%) while almost 40% have sensory disabilities. Eleven have multiple disabilities, while a few have health-related problems, learning disabilities and emotional and behavioral problems. The study concluded that the public special education schools offer limited programs and services to cater the sensory disabilities, mental deviations, and other health-related disabilities. It is recommended that further investigations be conducted to augment the preliminary findings.
Keywords: Special Education; disabilities; descriptive method; Philippines